Crenigacestat (LY3039478) inhibits osteogenic differentiation of human valve interstitial cells from patients with aortic valve calcification in vitro - Lobov, Arseniy A.; Boyarskaya, Nadezhda V.; Kachanova, Olga S.; Gromova, Ekaterina S.; Shishkova, Anastassia A.; Zainullina, Bozhana R.; Pishchugin, Alexander S.; Filippov, Alexey A.; Uspensky, Vladimir E.; Malashicheva, Anna B. (Frontiers in Cardiovascular Medicine, 2022)
Calcific aortic valve disease (CAVD) is one of the dangerous forms of vascular calcification. CAVD leads to calcification of the aortic valve and disturbance of blood flow. Despite high mortality, there is no targeted therapy against CAVD or vascular calcification. Osteogenic differentiation of valve interstitial cells (VICs) is one of the key factors of CAVD progression and inhibition of this process seems a fruitful target for potential therapy. By our previous study we assumed that inhibitors of Notch pathway might be effective to suppress aortic valve leaflet calcification. We tested CB-103 and crenigacestat (LY3039478), two selective inhibitors of Notch-signaling, for suppression of osteogenic differentiation of VICs isolated from patients with CAVD in vitro. Effect of inhibitors were assessed by the measurement of extracellular matrix calcification and osteogenic gene expression. For effective inhibitor (crenigacestat) we also performed MTT and proteomics study for better understanding of its effect on VICs in vitro. CB-103 did not affect osteogenic differentiation. Crenigacestat completely inhibited osteogenic differentiation (both matrix mineralization and Runx2 expression) in the dosages that had no obvious cytotoxicity. Using proteomics analysis, we found several osteogenic differentiation-related proteins associated with the effect of crenigacestat on VICs differentiation. Taking into account that crenigacestat is FDA approved and there are several clinical trials of crenigacestat for anti-tumor therapy, we argue that this drug could be considered as a potential inhibitor of cardiovascular calcification.